De Doctrina Christiana and Milton’s Canonical Works: Revisiting the Authorship Question - Clawson, James M.; Wilson, Hugh F. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
Since the discovery of De Doctrina Christiana almost 150 years after John Milton’s death, the Latin manuscript has commonly been attributed to the English writer—but not without controversy. For many scholars, the most recent phase of the debate seemed to end with the 2007 publication of Milton and the Manuscript of De Doctrina Christiana, which used stylometry to argue confidently for Milton’s authorship. This article is presented in dissent. Prompted by disjunctures in style and substance between the treatise and Milton’s canonical works, we revisit the authorship question. Using the complete text from the manuscript, a broader selection of candidates, and newer stylometric methods, we show some limitations of the earlier approach. Finally, drawing upon a neglected tradition of scholarship, we suggest that Jeremias Felbinger is a more plausible candidate for authorship, and we evaluate his candidacy through multiple stylometric tests.